Liver Transplantation in HIV Patients - Fox, Alyson N.; Vagefi, Parsia A.; Stock, Peter G. (Seminars in Liver Disease, 2012)
In the last three decades, the management of human immunodeficiency virus (HIV) has improved dramatically. The use of combination antiretroviral therapy (ART) has been successful at preventing death and the myriad infectious, malignant, and immune-mediated complications of HIV. Once considered to be a fatal disease, HIV is now considered by many to be a chronic disease; those affected may now live to experience complications of other coexistent diseases. Liver disease has been increasingly recognized as a leading cause of non-HIV/acquired immunodeficiency syndrome- (AIDS-) related morbidity and mortality in this population.123 Although liver transplantation offers the opportunity to prolong life, the transplant community has been slow to recognize the chronicity of HIV and potential for transplantation within this population. The experience with liver transplantation in HIV-positive patients is evolving and successful outcomes have been observed when specific criteria are used to select candidates.
Keywords: liver transplantation; HIV; viral hepatitis